P663Cardiac energy dependence on glucose increases metabolites related to glutathione and activates metabolic genes controlled by mTOR. (15th July 2014) - Schisler, J; Grevengoed, T; Ellis, J; Paul, D; Willis, M; Patterson, C; Coleman, R
Abstract: Long chain acyl-CoA synthetases (ACSL) catalyze long chain fatty acids (FA) conversion to acyl-CoAs. Temporal ACSL1 inactivation in mouse hearts (Acsl1H-/-) impaired FA oxidation (FAO) and dramatically increased glucose uptake, glucose oxidation, and mTOR activation, resulting in cardiac hypertrophy. Our objective was to elucidate the cardiac cellular response to increased glucose utilization in response to the genetic inactivation of FAO using metabolomics and gene expression analyses. Using metabolomics analysis, we identified 60 metabolites altered in Acsl1H-/- hearts, including 6 related to glucose metabolism and 11 to cysteine and glutathione pathways. Concurrently, global transcriptional analysis revealed differential expression of 568 genes in Acsl1H-/- hearts, a subset of which we hypothesized were targets of mTOR; subsequently, we measured the transcriptional response of several genes after chronic mTOR inhibition via rapamycin treatment during the period in which cardiac hypertrophy develops. Hearts from Acsl1H-/- mice increased expression of several Hif1α-responsive glycolytic genes regulated by mTOR; additionally, expression of Scl7a5, Gsta1/2, Gdf15, and starvation-response genes Fgf21, Asns, Trib3, Mthfd2, were strikingly increased by mTOR activation. The switch from FA to glucose utilization causes mTOR-dependent alterations in cardiac metabolism. We identified cardiac mTOR-regulated genes not previously identified in other cellular models, suggesting tissue-specific mTOR signaling. Increased glucose utilization also changed glutathione-related pathways and compensation by mTOR. The hypertrophy, oxidative stress, and metabolic changes that occur within the heart when glucose supplants FA as a major energy source suggests substrate switching to glucose may not be entirely benign